2009
DOI: 10.1098/rsta.2009.0093
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strain enhances survivability of collagen micronetworks in the presence of collagenase: implications for load-bearing matrix growth and stability

Abstract: There has been great interest in understanding the methods by which collagen-based load-bearing tissue is constructed, grown and maintained in vertebrate animals. To date, the responsibility for this process has largely been placed with mesenchymal fibroblastic cells that are thought to fully control the morphology of load-bearing extracellular matrix (ECM). However, given clear limitations in the ability of fibroblastic cells to precisely place or remove single collagen molecules to sculpt tissue, we have hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 63 publications
7
109
0
Order By: Relevance
“…Normal, physiologic loads are required to maintain tendon homeostasis and prevent excessive degradation of the extracellular matrix [25][26][27] . Nabeshima et al found that culturing nontensioned rabbit patellar tendon explants in the presence of collagenase over a period of twenty hours significantly decreased linear stiffness (p < 0.0001), elongation to failure (p < 0.002), and maximum failure force (p < 0.002) by 80% compared with explants tensioned with constant 4% strain 26 .…”
Section: Tendon Homeostasismentioning
confidence: 99%
“…Normal, physiologic loads are required to maintain tendon homeostasis and prevent excessive degradation of the extracellular matrix [25][26][27] . Nabeshima et al found that culturing nontensioned rabbit patellar tendon explants in the presence of collagenase over a period of twenty hours significantly decreased linear stiffness (p < 0.0001), elongation to failure (p < 0.002), and maximum failure force (p < 0.002) by 80% compared with explants tensioned with constant 4% strain 26 .…”
Section: Tendon Homeostasismentioning
confidence: 99%
“…A strain rate of 100 % strain/min is used ated on the mechanical data of the statically cultured isotropic and anisotropic constructs. The parameter k 3 refers to the degradation rate in absence of strain evaluated by Hadi et al (2012) on the basis of the experiments of Bhole et al (2009). Parameters k 4 and k 5 , describing the collagen degradation, were estimated using the experimental mechanical data of the biaxial isotropic statically loaded constructs and uniaxial cyclically loaded constructs, with strain applied along the scaffold fibers.…”
Section: Scaffold and Collagen Characterizationmentioning
confidence: 99%
“…The degradation of collagen fibers happens according to strain-dependent kinetics. When strain is applied to a collagen gel, the collagen fibers that are oriented in the direction of the strain will degrade slower than the collagen fibers in all the other directions (Bhole et al 2009;Hadi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The positive constants k 1 and k 2 are chosen to approximate experimental results such as [1]. The integral with respect to τ of just the survival kernel defines the so-called fiber orientation density function…”
Section: Materials Modelsmentioning
confidence: 99%
“…The fiber-remodeling process is described by a so-called survival kernel which is modeled in terms of a constant fiber creation rate and a fiber-stretch related fiber-dissolution rate. This dissolution rate is capable to approximate experimental observations, i.g., Bhole et al [1]. Previous studies of Topol et al [3,5] and Topol & Demirkoparan [4] focus on the development of the fiber properties for different isochoric deformation sequences.…”
Section: Introductionmentioning
confidence: 99%